A abordagem Theoprax nos cursos técnicos e de graduação tecnológica do Senai/Cimatec: o lugar da epistemologia e da inovação no processo de formação discente e na práxis docente - Santos, Maria de Fátima Luz (2015)
The focus of this dissertation is the Theoprax method in technical and technological programs in SENAI/Cimatec: The place of epistemology and innovation in the formation process of the student and in the teaching practice. The Theoprax method is embodied in teaching through projects, choosing real problems as challenging situations to mobilize significant learning in professional and technological education. Upon approaching this theme it is relevant to mention the interest in analyzing these programs within a multi-referential perspective, situating the phenomenon of education within its constitutive belonging. In this sense the investigation is mediated by qualitative and quantitative research aiming at appropriating the multiple languages of the subjects, besides other data and information. Toward this end, it makes use of the directive and non-directive interviews seeking to better apprehend the formative process and its manifestations mediated by the epistemology which feeds into the Theoprax method. The place of the epistemology takes on a meaning of the subjects belonging in their social practices. The place has a historical meaning of critical construction based on the movement of the subjects of the educational process in their interactions as organic intellectuals. In its turn, innovation is translated into transformation and changes in the formation process; therefore, it presupposes a dialog relation between students who express their interpretative comprehension and professors who expose themselves in sensitive listening. They are subjects who join a participant research project seeking meanings for a construction mediated by projects. The adoption of the Theoprax method by the SENAI/BA, in this emphasis, transgresses the reductionist view centered only on new competencies resulting from the impacts of the technological innovations in work and reinvents itself in the complexity of the knowledge which dialogs interdisciplinarally with other knowledges. In this way, it heads toward overcoming the practices based on the technicist and traditional tendency of the Liberal or Conservative Pedagogy and veers in the direction of Critical Pedagogy. For this, these transformations are carried out based on a critical awareness of the reality. Apprehending this reality in a multi-referenced way is the path to a dialectical relation and among other actors in education and from work. In this perspective, cooperative professional and technological education gain a meaning of innovation, being embodied by the weaving of the relations between the educational entity and productive entity, through resignified and new contracts, sustained by an ethics which is expressed in social responsibility. Therefore, the adoption of problematized teaching and by projects in professional and technological education mediated by the Theoprax method, is an initiative of the SENAI/Cimatec, in Bahia which dares to break new trails in professional and technological education constituting itself as the first Reference Center in Brazil.